Taxonomic notes on Tragopogon, and two newly described taxa from Anatolia. (3rd June 2016) - Gültepe, Mutlu; Coşkunçelebi, Kamil; Makbul, Serdar; Terzioğlu, Salih
Abstract : Tragopogon L. (Asteraceae) includes several cryptic species that are geographically widespread and morphologically similar. Here, we describe two new native species from eastern Anatolia. Through both morphological and molecular data, we present diagnostic characteristics, descriptions, pollen grains and micro‐ and macro‐morphological properties of achenes, as well as the conservation status of the newly described species. Current morphological and molecular results support treating T. reticulatus Boiss. & Huet and the two newly described taxa under the section Profundisulcati Kuthath. Molecular phylogentic reconstructions based on ITS data show that T. longirostris Sch. Bip. is a distinct species rather than a subspecies of T. porrifolius L. ( T. porrifolius subsp. longirostris (Sch. Bip.) Greuter) and that ligule colour is not a taxonomically important trait at the subrageneric level.